Analysis of Femoral Shaft Fractures in the Pediatric Population at a Tertiary Care Center: A Longitudinal Study - Pedro García-Benavides; Félix Gustavo Mora-Ríos; Nancy Daniela Zavala-Luna; Emilio Ignacio Pérez-Jimenez; Carlos Alberto Castro-Fuentes (Emergency Care and Medicine)
Background: Femoral shaft fractures are very common in the pediatric population; however, information is scarce. Methods: A total of 189 pediatric patient records were reviewed to identify the characteristics of diaphyseal fractures, including origin, type, pattern, surgical technique, and complications. Descriptive statistics were used to calculate frequencies and percentages. Meanwhile, continuous and categorical variables were analyzed using logistic regression to compare the different types of fractures in the population. Results: The proportion of males was higher compared to females (2:1). The highest prevalence was observed in the 10–14-year-old age group (n = 71; 37.5%). The primary mechanism of injury was traffic accidents (n = 93; 49.2%). Left femoral shaft fractures (n = 101; 53.4%) were the most prevalent. Transverse patterns predominated among the identified fractures (n = 105; 55.6%), most of which were closed fractures. Among the complications, non-union was the most frequent (n = 13; 6.9%), followed by wound infections (n = 3; 1.5%). Obesity (p < 0.001) and overweight (p < 0.001) were statistically significant in the left-sided femoral shaft fracture group. Conclusions: Non-union was the main complication identified in our study population. Obesity and overweight were identified as predictive variables for left-sided femoral shaft fractures. Meanwhile, none of the injury mechanisms showed statistical significance. Diaphyseal fractures in the pediatric population are underestimated, as well as the predictors causing them. Therefore, it is necessary to establish better management strategies for this type of fracture in pediatric patients.